Perancangan Pembuatan Sistem Informasi Akuntansi Pada PT X - Rosaline Debora Kusuma; Rudy Adipranata; Agustinus Noertjahyana (Jurnal Infra, 2015)
PT X is a company engaged in the sale, purchase of computer equipment. PT X also receive services for servicing computers and laptops. PT X has a problem in the transaction data integration between service, online sales and offline sales.To overcome these problems, made an application has the following scope : the process of buying, selling offline, online, settlement of accounts payable, purchase returns, stocks of goods and services, processes accounting, and financial statements that include general ledger, sales journal, a journal purchases, cash receipts journals, accounts payable, accounts receivable reports, inventory reports, sales reports, purchasing reports, income statement, owner's equity, balance sheet. This application is made by using the programming language PHP and MySQL as data storage.Applications are made to the application's test results show that the application can automatically process the purchase transaction data, offline sales, online, general journal, payment of debts, receivables and servicing. The level of accuracy, appropriateness and completeness of the financial statements produced very satisfactory application.